Patents, pills, poverty and pandemic: the ethical issues - Brown, Walter (Rhodes University, Faculty of Humanities, Department of Philosophy, 2003)
This thesis argues that corporations qua corporations are moral agents sui generis and hence capable of being held morally responsible. I argue that corporations qua corporations are responsible for the actual and foreseen consequences of their actions. I analyse normative theories and the different proscriptive responsibilities they place on moral agents and hence corporations. I examine Kantianism, utilitarianism and virtue ethics. I argue for a unique normative ethical theory that incorporates reasoning from all three of the normative theories. I argue for a broad range of reasons to factor into deciding whether an act is ethical or not. One of the claims of this thesis is that ethical theories must incorporate an agent's motivation, intention and character traits as relevant to deciding on whether an action is ethical or not. My thesis argues for an indispensable role for the virtues while at the same time incorporating impartial beneficence and universal rationality from utilitarianism and Kantianism. This position I, following the literature, refer to as moderate virtue theory. Having established corporate qua corporate responsibility I question the pharmaceutical corporation's practice of patenting life saving medication during a state of pandemic in poor countries. The moderate virtue theory position prioritises contexts and the actual human condition and criticises normative theories that attempt to give universal, abstracted answers to ethical problems. It is for this reason and the current (2003) HIV/AIDS pandemic that I focus on a particular context. I examine the practice of patenting life saving medication within South Africa and argue, applying moderate virtue theory, that this act cannot be justified. I argue that a pharmaceutical corporation that patents life saving medication in South Africa cannot justify that action and thus is morally responsible for that action. I also argue that corporations patenting HIV/AIDS medication in South Africa have unethical motivations and intentions.
Keywords: Kant, Immanuel, 1724-1804 -- Ethics; AIDS (Disease) -- Treatment -- South Africa -- Moral and ethical aspects; AIDS (Disease) -- Moral and ethical aspects; HIV infections -- South Africa; HIV infections -- Treatment -- South Africa -- Moral and ethical aspects; Social responsibility of business; Pharmaceutical industry -- South Africa -- Moral and ethical aspects